EXPRESSION OF Β-TUBULIN IN THE SENSORIMOTOR CORTEX OF THE CEREBRAL HEMATURIA IN THE MODELING OF TRANSIENT ISCHEMIA ON THE BACKGROUND OF SENSITIZATION OF BRAIN ANTIGEN AND IMMUNE CORRECTION OF THE CHANGES - Яременко, Л.М.; Грабовий, О.М.; Шепелєв, С.Є. (World of Medicine and Biology, 2017)
In order to analyze the dynamics of β-tubulin expression in the sensorimotor cortex during the modeling of transient ischemia against the background of previous sensitization by brain antigen and immunocorrection of their consequences, an experiment was performed on 185 white mature male rats weighing 260-290 g. Histological, immunohistochemical, densitometric and statistical methods of research. It was found that sensitization with brain antigen leads to diffuse degenerative changes in the cerebral cortex, accompanied by a decrease in β-tubulin expression. Previous sensitization by brain antigen leads to an increase in the severity of brain damage and a decrease in the expression of β-tubulin in acute circulatory disturbance. The use of immunophane provides a reduction in changes in β-tubulin expression in the sensorimotor cortex caused by both sensitization of the brain antigen and in combination with transient impairment of cerebral blood flow.